Glutamate antagonism fails to reverse mitochondrial dysfunction in late phase of experimental neonatal asphyxia in rats - Reddy N.R.; Krishnamurthy S.; Chourasia T.K.; Kumar A.; Joy K.P. (My University, 2025)
Neonatal asphyxia is a primary contributor to neonatal mortality and neuro-developmental disorders. It progresses in two distinct phases, as initial primary process and latter as the secondary process. A dynamic relationship exists between excitotoxicity and mitochondrial dysfunction during the progression of asphyxic injury. Study of status of glutamate and mitochondrial function in tandem during primary and secondary processes may give new leads to the treatment of asphyxia. Neonatal asphyxia was induced in rat pups on the day of birth by subjecting them to two episodes (10 min each) of anoxia, 24 h apart by passing 100% N 2 into an enclosed chamber. The NMDA antagonist ketamine (20 mg/kg/day) was administered either for 1 day or 7 days after anoxic exposure. Tissue glutamate and nitric oxide were estimated in the cerebral cortex, extra-cortex and cerebellum. The mitochondria from the above brain regions were used for the estimation of malondialdehyde, and activities of superoxide dismutase and succinate dehydrogenase. Mitochondrial membrane potential was evaluated by using Rhodamine dye. Anoxia during the primary process increased glutamate and nitric oxide levels; however the mitochondrial function was unaltered in terms of succinate dehydrogenase and membrane potential. Acute ketamine treatment reversed the increase in both glutamate and nitric oxide levels and partially attenuated mitochondrial function in terms of succinate dehydrogenase activity. The elevated glutamate and nitric oxide levels were maintained during the secondary process but however with concomitant loss of mitochondrial function. Repeated ketamine administration reversed glutamate levels only in the cerebral cortex, where as nitric oxide was decreased in all the brain regions. However, repeated ketamine administration was unable to reverse anoxia-induced mitochondrial dysfunction. The failure of glutamate antagonism in the treatment of asphyxia may be due to persistence of mitochondrial dysfunction. Therefore, additionally targeting mitochondrial function may prove to be therapeutically beneficial in the treatment of asphyxia. © 2011 Elsevier Ltd. All rights reserved.